The Potential of Binahong Leaf (Anredera cordifolia) Ethanol Extract on Male Fertility in Mice Exposed to E-Cigarette Smoke - I Gusti Ayu Widianti; Nyoman Gede Wardana; Ida Ayu Alit Widhiartini; Bagus Komang Satriyasa; Ni Wayan Sukma Antari; Made Sindy Astri Pratiwi (Media Publikasi Cendekia Indonesia, 2026)
Binahong leaf is known for its strong ability to prevent oxidation due to its active flavonoid compounds. Exposure to electronic cigarette smoke can increase reactive oxygen species (ROS), as a contributing factor to infertility. This study aims to identify the potential of Binahong leaf (Anredera cordifolia) ethanol extract on testosterone levels and spermatogenic cells in adult mice (Mus musculus) exposed to electronic cigarette smoke. A post-test control group design was used, with 28 male Balb/c mice allocated to four groups. The control group received 0.3% CMC, while the three treatment groups were administered Binahong leaf ethanol at doses of 50, 100, and 200 mg/kg body weight, in a volume of 0.1 ml orally each evening for 35 days. All mice were exposed to an electronic cigarette containing 6 mg of nicotine for 20 minutes. On day 36, blood samples were obtained to measure testosterone levels via ELISA. Testicular tissue was observed using Hematoxylin-Eosin staining. A marked elevation in testosterone concentrations and spermatogenic cell count was observed in the group treated with 50 mg/kg BW of Binahong leaf ethanol extract in contrast to the control group (p = 0.014 and 0.008, respectively). Higher doses reduced testosterone/spermatogenesis compared to the optimal dose, potentially implying a toxic or inhibitory effect. Binahong leaf ethanol extract administered at 50 mg/kg BW is effective in increasing testosterone levels and spermatogenic cells in adult mice (Mus musculus) exposed to electronic cigarette smoke.